PENDIDIKAN BERPRESPEKTIF GENDER DAN MULTIKULTURAL - Amiruddin Mustam (LPPM IAIN Parepare, 2015)
Education is a unique human activity in a community aims to humanize human, as an important instrument for the empowerment of communities, especially for marginalized communities. In addition, education is also an effort to get gender justice in society. Thus, formal education is a means to socialize as well as to transfer values and norms that prevail in society, including values and norms of gender and cultural diversity. All norms and values are transferred through the text books used as well as the atmosphere developed in learning process.